Kompetenz des Kartenzeichnens – Theoretische Grundlagen und Entwurf eines Kompetenzstufenmodells - Frank, Friedhelm; Obermaier, Gabriele; Raschke, Nicole (Zeitschrift für Geographiedidaktik (ZGD), 2010)
In this article some relevant theoretical considerations about map drawing are outlined. This includes aspects e.g. from writing competence and from geographical education. In chapter 3 results of international empirical studies to map drawing competence are discussed. Considerations about a competence model are made in chapter 4. On this basis an empirical study is planned, which is outlined in chapter 5.
Keywords: map skills, map draw competence, competence model, geographical competence